2018
DOI: 10.1212/wnl.0000000000006650
|View full text |Cite
|
Sign up to set email alerts
|

Migraine with visual aura is a risk factor for incident atrial fibrillation

Abstract: ObjectiveMigraine with visual aura is associated with cardioembolic stroke risk. The aim of this study was to test association between migraine with visual aura and atrial fibrillation (AF), in the Atherosclerosis Risk in Communities study.MethodsIn the Atherosclerosis Risk in Communities study, a longitudinal, community-based cohort study, participants were interviewed for migraine history in 1993–1995 and were followed for incident AF through 2013. AF was adjudicated using ECGs, discharge codes, and death ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 36 publications
4
76
4
2
Order By: Relevance
“…In the ARIC study, migraine with visual aura was associated with cardioembolic stroke (HR 1.7; 95% CI: 1.2‐2.6, P = .008), but not with thrombotic or lacunar subtypes, suggesting visual aura symptoms may be related to distal emboli in the posterior circulation 154 . The study also reported that MWA was associated with increased risk of new onset atrial fibrillation, an important stroke risk factor in the aged 155 . These findings, combined with the discovery that late‐life ischemic stroke was associated with late (rather than early) onset MWA, 156 implies that aura may be secondary to atrial fibrillation‐associated microembolism.…”
Section: Potential Mechanisms Of Migraine‐related Strokementioning
confidence: 94%
“…In the ARIC study, migraine with visual aura was associated with cardioembolic stroke (HR 1.7; 95% CI: 1.2‐2.6, P = .008), but not with thrombotic or lacunar subtypes, suggesting visual aura symptoms may be related to distal emboli in the posterior circulation 154 . The study also reported that MWA was associated with increased risk of new onset atrial fibrillation, an important stroke risk factor in the aged 155 . These findings, combined with the discovery that late‐life ischemic stroke was associated with late (rather than early) onset MWA, 156 implies that aura may be secondary to atrial fibrillation‐associated microembolism.…”
Section: Potential Mechanisms Of Migraine‐related Strokementioning
confidence: 94%
“…Observational studies have identified migraine as an independent risk factor for coronary artery disease (CAD) and atrial fibrillation (AF) . However, identifying causal relationships in observational settings can be challenging due to residual confounding, misclassification or reverse causality .…”
Section: Introductionmentioning
confidence: 99%
“…4 The increased incidence of atrial fibrillation and cardioembolism in patients diagnosed with migraine with aura was linked to acute stroke. 5,6 Migraine with aura can also be found as a stroke mimic during acute stroke management 7 ; however, only a few studies investigated the frequency and characteristics of migraine with aura in patients who initially presented with strokelike symptoms.…”
mentioning
confidence: 99%
“…4 Recent studies showed that migraine with aurainduced stroke may be associated with an increased risk of incidental atrial fibrillation and cardioembolic stroke. 5,6 Because we included patients diagnosed with migraine with aura who initially presented with stroke-like symptoms, all patients underwent ECG and multimodal CT scan, and more than half patients underwent DWI MRI. We found no patients with perfusion change or asymptomatic ischemic stroke.…”
mentioning
confidence: 99%